Analysis of Village Government Financial Management Performance in Deli Serdang - Nasution, Dito Aditia Darma; Welly, Yerisma; Sianipar, Martin Yehezkiel (Basic and Applied Accounting Research Journal, 2024)
The aim of this research is to determine the performance of village financial management in Batang Kuis District, Deli Serdang Regency. Data collection in this research used a questionnaire, namely the sample used a purposive sampling method, the research units were the Village Head, Village Secretariat, Village Treasurer or Head of Finance, Section Head, Head of Village Affairs and Village Consultative Body. The number of samples in this study (8 respondents in each village with a total of 9 villages), the analysis method used multiple regression. The results of the research found that Village Apparatus Capacity, Financial Reporting, Quality of BPD Supervision and Village Assistance have a positive and significant influence on village financial management performance in Batang Kuis District, Deli Serdang Regency, both partially and simultaneously.